Peeping over Galileo's shoulders: Laying the foundations of heliocentrism in elementary school - Pincelli, Michelina Marta (2020)
In this work, an adaptation of the first observation attempted by Galileo to demonstrate the heliocentric hypothesis to be correct is developed. The objective of the proposal is to let students transiting the last year of the primary school confront by themselves the same contradicting scenario that put Galileo at crossroads during the second decade of the 17th century. Results of its implementation on two courses encompassing 32 students with ages 11-12 are reported and first impressions of this pedagogical approach are analyzed.